1996
DOI: 10.1111/j.1349-7006.1996.tb03116.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Controls of Susceptibility and Resistance to 4‐Nitroquinoline 1‐Oxide‐induced Tongue Carcinomas in Rats

Abstract: We analyzed the incidence of infiltrative mass‐type tongue carcinomas (IMTC) induced in 550 rats by continuous oral administration of 0.001% 4‐nitroquinoline 1‐oxide solution for 180 days. The study included various crosses of susceptible Dark‐Agouti rats (DA) and resistant Wistar/Furth rats (WF). DA showed a 93.6% incidence of IMTC measuring more than 5 mm in their largest diameter, while WF showed only a 4% incidence. Reciprocal F1 and F2 hybrids mated by DA and WF showed 47.5% and 45.8% incidences, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Dark Agouti (DA) rats are highly susceptible to 4NQO-induced tongue cancer (TC), whereas Wistar-Furth rats (WF) are very resistant (3,4). A genome-wide association study in F2 progeny of these 2 strains revealed 5 significant QTLs, namely Tscc1-5 ( Tcas1-5 in the Rat Genome Database), which account for differences in susceptibility to TC (2,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Dark Agouti (DA) rats are highly susceptible to 4NQO-induced tongue cancer (TC), whereas Wistar-Furth rats (WF) are very resistant (3,4). A genome-wide association study in F2 progeny of these 2 strains revealed 5 significant QTLs, namely Tscc1-5 ( Tcas1-5 in the Rat Genome Database), which account for differences in susceptibility to TC (2,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic effect of Tscc4 on the size of TCs was below a signifi cance level (lod score, 3.13). a Cited from Kitano et al [7] with copyright permission of the publisher. On RNO14, we mapped a fi fth QTL ( Tscc5 ) linked to the number of TCs.…”
Section: Qtl Determining Host Susceptibility To Tcsmentioning
confidence: 99%
“…WF) F 1 hybrid rats were examined for loss of heterozygosity (LOH) at each chromosomal region containing these QTL. This report reviews our extensive genetic analysis of rat 4NQO-induced TCs and discusses possible candidate genes with special reference to genetic alterations in TCs and the metabolic activation of the carcinogen [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually 100% of DA rats given drinking water containing 0.001% 4NQO developed one or more large TC within 180 days of administration, whereas the Wistar/Furth (WF) strain of rats was much less susceptible. [5][6][7][8] In the previous study with reciprocal backcrosses between DA and WF rats, 7,8) DA rats were shown to have a semidominant susceptibility locus, Stc1 (Susceptibility to TC-1) on rat chromosome (RNO) 19, and WF rats, another semidominant resistance gene Rtc1 (Resistance to TC-1) on RNO1.In this study, to scrutinize further the genetic predisposition to TC in the rat, we studied F2 progeny between DA and WF strains by means of a composite interval mapping analysis. After several statistical trials, we employed a quantitative parameter for tumor number, TC >3 mm in diameter, rather than TC >5 mm.…”
mentioning
confidence: 99%